A malaria parasite subtilisin propeptide-like protein is a potent inhibitor of the egress protease SUB1. Issue 2 (31st January 2020) - Tarr, Sarah J.; Withers-Martinez, Chrislaine; Flynn, Helen R.; Snijders, Ambrosius P.; Masino, Laura; Koussis, Konstantinos; Conway, David J.; Blackman, Michael J.
Abstract : Subtilisin-like serine peptidases (subtilases) play important roles in the life cycle of many organisms, including the protozoan parasites that are the causative agent of malaria, Plasmodium spp. As with other peptidases, subtilase proteolytic activity has to be tightly regulated in order to prevent potentially deleterious uncontrolled protein degradation. Maturation of most subtilases requires the presence of an N-terminal propeptide that facilitates folding of the catalytic domain. Following its proteolytic cleavage, the propeptide acts as a transient, tightly bound inhibitor until its eventual complete removal to generate active protease. Here we report the identification of a stand-alone malaria parasite propeptide-like protein, called SUB1-ProM, encoded by a conserved gene that lies in a highly syntenic locus adjacent to three of the four subtilisin-like genes in the Plasmodium genome. Template-based modelling and ab initio structure prediction showed that the SUB1-ProM core structure is most similar to the X-ray crystal structure of the propeptide of SUB1, an essential parasite subtilase that is discharged into the parasitophorous vacuole (PV) to trigger parasite release (egress) from infected host cells. Recombinant Plasmodium falciparum SUB1-ProM was found to be a fast-binding, potent inhibitor of P. falciparum SUB1, but not of the only other essential blood-stage parasite subtilase, SUB2, or of other proteases examined. Mass-spectrometry and immunofluorescence showed that SUB1-ProM is expressed in the PV of blood stage P. falciparum, where it may act as an endogenous inhibitor to regulate SUB1 activity in the parasite.